Environmental design framework for public hospitals in Malaysia / Jamaludin Muhamad - Muhamad, Jamaludin (2022)
The main priority of Hospital design quality in Malaysia is to arrange passive design for staff and patient-oriented care design that requires a user-friendly environment. Although there are various quality design evaluations, evaluating success criteria has brought a new dimension to tracking the quality used by exploring the user experience. Furthermore, the method does not have a procedure to identify users' needs effectively. Still, it will lead to quality and energy efficiency dimensions that need to be considered in its implementation. Therefore, this research aims to achieve energy efficiency through the experiences of patients and staff in public hospital ward spaces. The nature of the staff and patient experience can influence the quality and energy efficiency of the hospital environment. The theory section suggests that the experience of hospital end users may be understood through their feedback on the status of the hospital environment by extending the theory of passive design and quality. This research uses five success criteria passive design identified from the literature. After synthesizing the literature, verification from the expert panel from each sector, namely the Public Work Department (Healthcare Facilities Projects), Medical Planner (Architect), and Consultant (Architect) who are directly involved in hospital design, is implemented. The qualitative method, interviews with an expert panel (n = 8), was conducted to find out the criteria of passive design are adapted to the creation of public hospitals implemented. Next, the data were analyzed using NVivo 12 to be part of the questionnaire developed. In addition, the success parameters of passive design were made through a questionnaire in the context of user experience of using the physical environment for energy efficiency in the Hospital. It is to find out that the impact of the design of this hospital is experienced by users who use it. A phenomenological philosophy and quantitative approach with case studies were conducted in three Malaysian public hospitals. Questionnaires were given to staff and patients (n = 154) involved in the hospital ward, and the data obtained was taken from the perspective of the user experience was conducted. Data were analyzed using factor analysis conducted by SPSS as this is the best way to get holistic information related to user experience. Research findings have been studied, and a refined framework of passive design success criteria has been conducted and confirmed a practical approach to this user experience method. The main contribution of this study is that the success criteria have provided added value in evaluating experiences among staff and patients, quality design evaluation, designing, building, and managing hospitals for energy efficiency. Therefore, this study should help organizations understand the needs of end-users and support the design of a user-friendly environment. Furthermore, this research provides a starting point from different backgrounds with more perspectives from the point of view of other actors.